Mathematical model for co-infection of HIV/AIDS and pneumonia with treatment - Onyinge, David O.; Ongati, Naftali O.; Odundo, Francis (International Journal of Scientific Engineering and Applied Science, 2016)
Pneumonia occurs commonly in HIV-infected patients. In this paper, we study a simple mathematical model for the co-infection of HIV/AIDS and Pneumonia. We establish that the model is well presented epidemiologically and mathematically. The disease-free equilibrium point is determined. We establish the basic reproduction number R0 for the model, which is a measure of the course of co-infection.
Keywords: HIV/AIDS –Pneumonia model; Coinfection; basic reproduction number; stability